Agresividad y el desarrollo emocional de los niños del proyecto ETIE del patronato de amparo social, GAD Municipal La Maná - Chicaiza Villaprado, Paola Anabel (2019)
The research project Aggressiveness and emotional development of the children of the ETIE project of the Social Protection Board, GAD Municipal "La Maná" was developed with the aim of diagnosing the influence of aggression on the emotions of children to improve academic performance and the family coexistence, through the theoretical compilation. Emotional development as a reflection of the achievements that children achieve within educational processes, aggressive behaviors have a negative effect on this indicator due to certain characteristics associated with their behavior as a negative position towards school, where they are easily distracted by academic activities, have difficulty focusing their attention on the classroom process, in addition to that, aggressive behavior alters the school climate and represent a risk factor for learning for all children in the group. Within the research process a mixed methodology was used, taking both qualitative and quantitative contributions, and with the application of data collection instruments such as the survey applied to parents, teachers and children participating in the municipal program, as well as establish causal relationships for the development of aggressive behaviors that are mostly environmental and family factors such as lack of emotional stability in the home or overexposure to inappropriate television programs which children manifest physical and psychological provocations. Finally we can conclude that aggressiveness is a complex behavior that can be the product of genetic factors such as behavior, within the social factors, is the school and the environment that surrounds it, in the family factor are immersed parents, brothers, in that they play a fundamental role in the child's development since the family is the basis of positive or negative behavior.